Suppression of EGFR/PKC-δ/NF-κB Signaling Associated With Imipramine-Inhibited Progression of Non-Small Cell Lung Cancer - Yueh, Po-Fu; Lee, Yuan-Hao; Chiang, I-Tsang; Chen, Wei-Ting; Lan, Keng-Li; Chen, Cheng-Hsien; Hsu, Fei-Ting (Frontiers in Oncology, 2021)
Background: Anti-depressants have been reported to own anti-tumor potential types of cancers; however, the role of imipramine in non-small cell lung cancer (NSCLC) has not been elucidated. Epidermal growth factor receptor (EGFR) was known to be one of the key regulators that control NSCLC progression. Whether EGFR would be the target of imipramine for suppressing tumor signaling transduction and results in anti-tumor potential is remaining unclear. Methods: We used CL-1-5-F4 cells and animal models to identify the underlying mechanism and therapeutic efficacy of imipramine. Cytotoxicity, apoptosis, invasion/migration, DNA damage, nuclear translocation of NF-κB, activation of NF-κB, phosphorylation of EGFR/PKC-δ/NF-κB was assayed by MTT, flow cytometry, transwell, wound healing assay, comet assay, immunofluorescence staining, NF-κB reporter gene assay and Western blotting, respectively. Tumor growth was validated by CL-1-5-F4/NF-κB-luc2 bearing animal model. Results: Imipramine effectively induces apoptosis of NSCLC cells via both intrinsic and extrinsic apoptosis signaling. DNA damage was increased, while, invasion and migration potential of NSCLC cells was suppressed by imipramine. The phosphorylation of EGFR/PKC-δ/NF-κB and their downstream proteins were all decreased by imipramine. Superior tumor growth inhibition was found in imipramine as compared to standard therapy erlotinib (EGFR inhibitor). Non-obvious body weight loss and liver pathology change were found in imipramine treatment mice. Conclusion: Imipramine-triggered progression inhibition of NSCLC both in vitro and in vivo are at least partially attributed to its suppression of EGFR/PKC-δ/NF-κB pathway.